The Effect of Pornography Discourse on the Reception of Stencil Novels by Enny Arrow - Anggraini, Ariska Puspita; Susanto, Dwi; Rais, Wakit Abdullah (Bina Nusantara University, 2021)
The research aimed to analyze pornography discourse in the reception of Enny Arrowâ€™s stencil novels between two millennial men. This was a qualitative research. The research sample focused on two millennial men in Surakarta who read the stencil novels intensively. Data were obtained by interview, and observations were conducted over six months. The research observed two newly recognized millennial men to read and interpret the stencil novels. After that, the research looked at the effect on the social relationships of the participants. The theory used to analyze the data was Normand Hollandâ€™s psychoanalytic literary reception. After data analysis process, it is revealed that pornography discourse makes the participants think that the stencil novels are entertaining but can be a taboo subject to discuss with others. Because of the pornography discourse, participants also think that story on the stencil novels should not be used as a general topic conversation.Â